2016
DOI: 10.1159/000445505
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Risk Factors for Conversion of Laparoscopic Cholecystectomy to Open Surgery - A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Background: Preoperative risk factors for the conversion of laparoscopic cholecystectomy to open surgery have been identified, but never been explored systematically. Our objective was to systematically present the evidence of preoperative risk factors for conversion of laparoscopic cholecystectomy to open surgery. Methods: PubMed and Embase were searched systematically in March 2014. Observational studies evaluating preoperative risk factors for conversion of laparoscopic cholecystectomy to open surgery in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 47 publications
4
51
5
1
Order By: Relevance
“…The results showed that male patients, age 60-65 years, sclerotic gallbladder or wall thickness (4-5 mm) and acute cholecystitis, were significant risk factors for conversion[54]. …”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that male patients, age 60-65 years, sclerotic gallbladder or wall thickness (4-5 mm) and acute cholecystitis, were significant risk factors for conversion[54]. …”
Section: Complicationsmentioning
confidence: 99%
“…It has been difficult to establish the role of percutaneous gallbladder drainage because of the different existing definitions for the “high-risk patient”[42,54]. In an attempt to clarify the conflicting evidences, Yeo et al[57] 2017 in a retrospective review, studied 103 aged patients (median: 80 years), who had undergone PC procedures.…”
Section: When To Perform Cholecystostomymentioning
confidence: 99%
“…This high rate may have resulted in increased perioperative morbidity, as OC compared to LC for acute cholecystitis is associated with increased risk of complications (28 vs. 18%, p = 0.03) [27] . A recent meta-analysis of observational studies showed that advanced age is associated with increased risk of conversion, although no obvious explanation is given [28] . Dense adhesions due to previous episodes of complicated gallstone disease or previous abdominal surgery, or perioperative cardiopulmonary complications may be the reason [19,21] .…”
Section: Discussionmentioning
confidence: 99%
“…Predicting the ‘difficult’ gallbladder in patients who present with AC is problematic and has important implications for resource allocation if an immediate cholecystectomy policy is adopted. Delay beyond 72 h after onset of symptoms, radiological evidence of inflammation, age >65 years, male gender and severe AC have been shown to be risk factors for conversion from laparoscopic to an open operation …”
Section: Introductionmentioning
confidence: 99%